'Somebody that looks like me' matters: a qualitative study of black women's preferences for receiving sexual health services in the USA. Issue 1 (4th January 2022) - Townes, Ashley; Guerra-Reyes, Lucia; Murray, Maresa; Rosenberg, Molly; Wright, Brittanni; Long, Lauren; Herbenick, Debby
Abstract: Research dedicated to understanding the sexual experiences of Black women has historically been framed around adverse outcomes. There are limited data that can be used to understand the lived experiences of Black women related to sexual health care. Twenty-five Black women aged 18- 35 from across nine US states were interviewed to gain insight into their experiences and preferences for receiving sexual health services. Three themes were developed from their accounts: individual and structural barriers affect access to and perceived quality of care; service provider race and gender impact sexual health care experiences; and personalised care improves engagement. Findings suggest the need for culturally informed training for sexual health practitioners working with Black women.